THE QUALITY OF ENVIRONMENT AS A VALUE IN THE CONSUMER’S SOCIETY: ECOLOGICAL, ECONOMIC AND CULTURAL-EDUCATIVE DIMENSIONS - Pruskus, Valdas (Acta Paedagogica Vilnensia, 2008)
The quality of environment as a value in consumer’s society and its ecological, economic and cultural- educative dimensions are discussed in the paper. The quality of environment in the consumer’s society is universal and not a single man’s worth, because it is related with the society and its future. The economic and cultural state of the society mainly depends on the quality of the environment. But the quality of the environment in the market conditions has its own value – it should be paid for it. This arises tension among business efforts to monitor ecological values and the rights of the citizens for the qualitative environment which is an expression of the born right for a secure space of existence. The quality of environment is defined by three dimensions – ecological, economic and cultural-educative. Though these dimensions are interdependent, they also express different worth aspects. The ecological worth of environment quality lies in how unblemished and unique functioning of ecosystem is secured. Economic worth is how effectively this environment is used, what services for a visitor it can offer, mostly needed for cognition of objects of nature and for the acquisition of new experiences. Cultural-educative worth is defined by three essential things. Firstly, the objects of nature are related with significant historical events and become valuable in the society as having not only aesthetic, but also spiritual and historical value. In this way, the natural environment acquires an educative value. Secondly, it is the institutional environment of the security of the objects of nature. The more effectively the institution of environment protection functions, the more ecological, cultural and economic worth of it, as an institution is growing up. Thirdly, the educative preparation of the citizens is very important. Highly ecologically educated citizen will give cultural worth priority for the quality of living environment.The institutions of a democratic government are oriented that the quality of environment would not be only declarative, but also become a priority and public interest. In this case a support would be given to the educational institutions and a favorable psychological medium would be formed for the youth’s valu-able standpoint towards the quality of the environment.
Keywords: education; value; quality of environment; consumer’s society; market; democratic; economical and cultural value; institutional environment; education institutes; ecological consciousness